2017
DOI: 10.3390/ijms18112271
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of the Interaction between Thioflavin T and an Amyloid Protein by Using High-Sensitivity Rheo-NMR

Abstract: Amyloid fibril formation is associated with numerous neurodegenerative diseases. To elucidate the mechanism of fibril formation, the thioflavin T (ThT) fluorescence assay is widely used. ThT is a fluorescent dye that selectively binds to amyloid fibrils and exhibits fluorescence enhancement, which enables quantitative analysis of the fibril formation process. However, the detailed binding mechanism has remained unclear. Here we acquire real-time profiles of fibril formation of superoxide dismutase 1 (SOD1) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…Because the secondary structure of Aβ determines its cytotoxicity, changes in CSF flow due to aging or disorders , may increase toxicity by altering Aβ conformation. Furthermore, flow increases intermolecular alignment and decreases the energy barrier for nucleation, the molecular effects of which have been confirmed via the flow-dependent modulation of nucleation, fibril growth, and other intra- and intermolecular processes of Aβ and other biological macromolecules. However, these studies examined Aβ in the absence of a cell membrane ( i.e. , stirring or shaking bath; Figure ) and did not evaluate the role of flowing condition on Aβ–lipid interactions and flow-triggered cytotoxicity.…”
mentioning
confidence: 99%
“…Because the secondary structure of Aβ determines its cytotoxicity, changes in CSF flow due to aging or disorders , may increase toxicity by altering Aβ conformation. Furthermore, flow increases intermolecular alignment and decreases the energy barrier for nucleation, the molecular effects of which have been confirmed via the flow-dependent modulation of nucleation, fibril growth, and other intra- and intermolecular processes of Aβ and other biological macromolecules. However, these studies examined Aβ in the absence of a cell membrane ( i.e. , stirring or shaking bath; Figure ) and did not evaluate the role of flowing condition on Aβ–lipid interactions and flow-triggered cytotoxicity.…”
mentioning
confidence: 99%
“…Shear stress has been reported to induce fibril aggregation of the whey protein beta-lactoglobulin 29 , 33 . A rheo NMR study of superoxide dismutase 1 (SOD1) showed that shear stress can induce the formation of amyloid fibrils from SOD1 monomers, while under static conditions there is no change in the monomer state 34 . Therefore, it is possible that shear stress caused by pipetting induced the transition to the amorphous aggregate state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to crowding effects, other factors may contribute to protein aggregation inside living cells, including chemical (e.g., decreased pH , ) and mechanical (e.g., shear or stretch ) factors. Indeed, aggregation of SOD1 has a strong dependence on pH, and we previously observed aggregate formation of SOD1 under dilute experimental conditions applying shear flow . To further understand the real conformational behavior of SOD1 inside living cells, R 2 relaxation dispersion measurements in living cells should be used to acquire information on the off-pathway transitions of SOD1 in situ .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aggregation of SOD1 has a strong dependence on pH, 92 and we previously observed aggregate formation of SOD1 under dilute experimental conditions applying shear flow. 93 To further understand the real conformational behavior of SOD1 inside living cells, R 2 relaxation dispersion measurements in living cells should be used to acquire information on the off-pathway transitions of SOD1 in situ.…”
mentioning
confidence: 99%